Dry and Wet atmospheric nitrogen deposition in Africa - (:unkn) unknown (My University, 2003)
This work is part of the IDAF* (IGAC/DEBITS/AFrica) programme which started in 1995 with the establishment of 10 measurement sites representative of major African ecosystems. The objectives of the programme are to study dry and wet deposition of important trace species and more generally the biogeochemical cycles of key nutrients. In this way, the IDAF activity is based on high quality measurements of atmospheric chemical data (gaseous, precipitation and aerosols chemical composition) on the basis of a multi-year monitoring. In this paper, our objective is to present the first estimation of the atmospheric nitrogen deposition budget in Africa based on experimental measurements. To estimate atmospheric nitrogen deposition, including both wet and dry processes, we compiled the IDAF nitrogen data (rain, particles and gases) obtained from the network for three consecutive years: 1998, 1999 and 2000. In western and central Africa, we studied a transect going from dry savanna (Niger and Mali) to humid savanna (Ivory Coast and Central Republic of Africa) and forest (Congo and Cameroon). In South Africa, two IDAF very different sites were chosen to be representative on one hand of a rural (semi-arid savanna) and on the other hand of an industrialized site. Presenting the different components of the nitrogen atmospheric deposition on these sites, i.e, dry deposition in gaseous (NO2, NH3, HNO3) and particulate forms (pNH4+, pNO3-) associated with wet deposition (NH4+, NO3-), this study allows us to give the relative contribution of dry and wet deposition processes to the total nitrogen deposition. The nitrogen atmospheric deposition presented for all the IDAF sites of the african continent range from 8 to 19 kgN.ha-1.yr-1. Sites from dry savanna in South Africa and West Africa have similar values (around 8-9 kgN.ha-1.yr-1 ) which are found in the lower part of the range. Wet zones from savanna and forests give values in the upper range (15 to 19 kgN.ha-1.yr-1).
Keywords: African Research